TINJAUAN LATIHAN KLASIFIKASI DESAIN MONOGRAM - Brian Alvin Hananto (Universitas Bunda Mulia, 2020)
Typography is one of the essential subjects for the education of visual communication designers and graphic designers. From the previous class-action research, the author studies the result of various monograms designers by students and formulated a monogram design classification based on the research. In the second cycle of the research, the author had developed an assignment that is intended to review the monogram design classification. The assignment was participated by 83 students, and the designs made by the students were the primary source of observations for the author to see how the monogram design classification had contributed to the visual explorations conducted by the students. The author also deployed questionnaires that 62 of the students had filled as supplementary feedback of the assignment and overall class. From the observation and the questionnaire feedbacks, the author had found new issues and limitations toward the monogram design classifications that the author had formulated before. From this second cycle of class action research, the author had reached a different conclusion from the first cycle of the research and issued a new conclusion that can be applied for other typographic visual explorations.